2009
DOI: 10.3844/ajavsp.2009.32.36
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hematological Values, Morphometric and Morphological Observation of the Blood Cell in Capture and Culture Asian Eel, Monopterus albus (Zuiew)

Abstract: Problem statement: Monopterus albus (Zuiew), Asian Eel, is one of the common fish found mainly in Asia. At present, the habitats of Asian Eels have been on the decrease. Contrarily, consumption of Asian Eel has increased. Whereas, data regarding blood cell characteristics, blood cell sizes and hematological values of Asian Eel are limited. As such, the objective of this study was to establish the blood cell characteristics, blood cell dimension and hematological values of capture and culture Asian Eel. Basic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…Similar findings which support our study has also reported by Gautam and Kumar who studied haematology of Channa punctatus subjected to Nuvan [21]. Recently, Ponsen et al studied haematological parameters and blood morphology of Asian eel, Monopterus alba and the results recorded are in agreement with our study [22]. Sasikala et al observed similar results in metasystox induced Channa striata [23].…”
Section: Morphometric Alterations In Erythrocytessupporting
confidence: 93%
“…Similar findings which support our study has also reported by Gautam and Kumar who studied haematology of Channa punctatus subjected to Nuvan [21]. Recently, Ponsen et al studied haematological parameters and blood morphology of Asian eel, Monopterus alba and the results recorded are in agreement with our study [22]. Sasikala et al observed similar results in metasystox induced Channa striata [23].…”
Section: Morphometric Alterations In Erythrocytessupporting
confidence: 93%
“…Kim gave an example by revealing the cellular composition of the internal primo-node by using the Giemsa stain. Giemsa stain has a remarkable dynamic range of colors capable of visualizing the complex morphological composition of blood cells ( Table 1 ) [ 43 , 60 62 ]. Figure 6 identifies a multipotent hematopoietic stem cell, hemocytoblast, and an important member of myeloid lineage, megakaryocyte [ 5 , 7 ].…”
Section: Primo-vascular Systemsmentioning
confidence: 99%
“…In the genus Anguilla, some species are recorded to have eosinophils while others lack this cell type (Orecka-Grabida, 1986;Kusuda and Ikeda, 1987;van Ginniken et al, 2005;Ponsen et al, 2009). Further sampling during other seasons or experimental exposure to pathogens or parasites might allow for the discovery of the existence of eosinophils and the basophils in all three fish species analyzed here.…”
Section: IImentioning
confidence: 90%
“…The neutrophil (heterophil) subtype with an intensively basophilic cytoplasm, resembling reptilian or avian azurophils, was found in moray and was difficult to classify as any known fish granulocyte type (Campbell and Ellis, 2007). Interestingly, these cells were not present in conger or common eel (Orecka-Grabida, 1986;Kusuda and Ikeda, 1987;van Ginniken et al, 2005;§ahan et al, 2007;Ponsen et al, 2009). Occasionally, there are granulocyte cells that do not fit into any of the subclasses and do not resemble any known granulocyte type (Ranzani-Paiva et al, 2003;Shigdar et al, 2009).…”
Section: IImentioning
confidence: 91%